Disseminated Mycobacterium chimaera Infection After Cardiothoracic Surgery. (16th June 2016) - Tan, Nicholas; Sampath, Rahul; Abu Saleh, Omar M.; Tweet, Marysia S.; Jevremovic, Dragan; Alniemi, Saba; Wengenack, Nancy L.; Sampathkumar, Priya; Badley, Andrew D.
Abstract: Ten case reports of disseminated Mycobacterium chimaera infections associated with cardiovascular surgery were published from Europe. We report 3 cases of disseminated M chimaera infections with histories of aortic graft and/or valvular surgery within the United States. Two of 3 patients demonstrated ocular involvement, a potentially important clinical finding.